Midwinter Spring, The Still Point and Dante. The Aspiration to the Eternal Present in T.S. Eliot’s Four Quartets - Llorens-Cubedo, Dídac (Miscelánea: A Journal of English and American Studies, 2014)
The imagery of Four Quartets makes T. S. Eliot’s indebtedness to Dante’s poetic imagination evident. Among the images of Dantean inspiration, the “still point” and “midwinter spring” effectively express the concept of an eternal present, central to Eliot’s poetic sequence. In the Quartets, opposites are reconciled and “past and future are gathered” at “the still point”. This still point can be related to the image associated with God in canto XXVIII of Dante’s Paradiso: a point of dazzling light. Midwinter spring, on the other hand, represents a state of spiritual fulfilment, out of time and space, and its depiction can be assumed to echo St Benedict’s words in canto XXII of Paradiso. Both the still point and midwinter spring hint at the same referent (eternal present, or the timeless) and show that Eliot’s fascination with the philosophical concept of time combines with his admiration for Dante’s powerful imagination.